Preparation method of zinc-nickel battery negative electrode
By using polymer slurry medium and high-speed stirring technology in the preparation method of zinc-nickel battery negative electrode, the problem of poor slurry coating performance and insufficient bonding tightness in the prior art is solved, and a higher load capacity and more stable electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510034131.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-09
AI Technical Summary
In the existing methods for preparing negative electrodes of zinc-nickel batteries, the slurry coating performance is poor, the electrode sheet bonding tightness is poor, and the substance dispersion is insufficient, resulting in low load capacity and unstable electrochemical performance.
A method for preparing a zinc-nickel battery negative electrode is adopted to prepare a polymer slurry medium by stirring the solid negative electrode active material and the negative electrode additive evenly, and the mixed powder is added to the slurry medium under high-speed stirring to avoid agglomeration. Then, SBR emulsion and PTFE emulsion are added to prepare a battery negative electrode slurry.
The load capacity and electrochemical performance of the electrode sheet are improved, the coating performance of the slurry and the dispersion uniformity of the substance are enhanced, the cycle life of the electrode sheet is extended and the stability is improved.
Smart Images

Figure CN119864377A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a method for preparing a negative electrode of a zinc-nickel battery. Background Art
[0002] In recent years, with the strong rise of new energy, and in order to meet the requirements of green development in the era, various energy storage batteries and power batteries have ushered in great development opportunities. Among them, zinc-nickel secondary batteries have the advantages of low self-discharge, low cost, high open circuit voltage and discharge current, and more importantly, high safety, and have good application prospects in the field of energy storage and power batteries.
[0003] As a potential energy battery, zinc-nickel battery has a simple manufacturing process, among which the slurry mixing process is one of the most important processes. The general slurry mixing is divided into water medium slurry mixing and organic medium slurry mixing. The negative electrode material often has different components. If the components are not fully and evenly dispersed, the stability of the electrode will be greatly affected.
[0004] Usually, if there are too many components in the slurry, the slurry mixing process will be much more difficult and the slurry mixing time will be much longer. It will be more difficult to disperse the components evenly, which will affect the subsequent performance and economic benefits.
[0005] In the prior art, the negative electrode slurry of zinc-nickel batteries does not consider the introduction of a high proportion of organic polymer slurry medium, and no organic framework is formed. The slurry often has a large fluidity. Although it is easy to fully stir evenly, the slurry with high fluidity is only suitable for coating in the form of slurry pulling. Such coating method also limits the load capacity of the electrode sheet. The paste-like slurry with poor fluidity is limited to the production of laminated batteries and is difficult to use in thinner wound batteries.
[0006] For example, in the prior art CN105161702A zinc-nickel battery, polyols are added to the negative electrode active material to maintain the uniform stability of the negative electrode active material during slurry mixing, so that the slurry can maintain its initial state for a long time, ensuring the consistency of electrode production, thereby fundamentally ensuring the consistency of the battery and improving the cycle stability of the power system.
[0007] Another example is the preparation method of the prior art CN110289395B, which includes the following steps: mixing and stirring the negative electrode powder and the additive to obtain the raw material powder; mixing and stirring the raw material powder and the polytetrafluoroethylene emulsion to obtain the mixed powder, wherein the revolution speed is 20-50 rad / min, the rotation speed is 3000-5000 rad / min, and the revolution and rotation time is 10-20 min; mixing and stirring the mixed powder and the paste medium to obtain the paste; the paste composition includes 77-85% of the negative electrode powder, 5-10% of the additive, 1-5% of the polytetrafluoroethylene and 8-17% of the paste medium by mass percentage. The problem that the paste prepared by the prior art has a low viscosity and is only suitable for preparing the pole piece by the method of pulling the paddle is solved, and the pole piece prepared is thin, the activity is low, the life is short and the consistency is poor.
[0008] For example, the prior art CN119050286 discloses a nickel-zinc battery positive electrode and its preparation method and application. The preparation method is relatively simple and the negative electrode slurry is not optimized and adjusted.
[0009] Another example is the prior art CN119050286A which discloses a negative electrode formula for a zinc-nickel secondary battery, in which PAAK is added to the solution before slurrying, and then the negative electrode powder is added and stirred to form a slurry. However, the addition of PAAK will lead to a more obvious agglomeration phenomenon, which will increase the difficulty of slurrying, not only affecting the performance of the electrode, but also leading to more cost increases.
[0010] In general, this field urgently needs to develop a method for preparing zinc-nickel battery negative electrodes with good slurry coating performance, tightly bonded negative electrode sheets, uniform material dispersion, and effectively increased loading capacity. Summary of the invention
[0011] In order to solve the above-mentioned deficiencies and shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a negative electrode for a zinc-nickel battery, which has good slurry coating performance, the prepared negative electrode plate is tightly combined, the material is evenly dispersed, and the load capacity and the electrochemical performance of the plate are effectively improved.
[0012] The technical solution adopted by the present invention is as follows:
[0013] A method for preparing a negative electrode of a zinc-nickel battery comprises the following steps:
[0014] Step (1): negative electrode powder mixing: the solid negative electrode active material and the negative electrode additive are fully stirred to obtain a negative electrode mixed powder; then the zinc powder and the carbon material are also pre-mixed to obtain a negative electrode mixed powder;
[0015] Step (2): preparing a polymer slurry medium: preparing different solutions in the polymer slurry medium in advance, mixing and stirring the different solutions to obtain a polymer slurry medium:
[0016] Step (3): slurry preparation, adding a surfactant sodium dodecylbenzene sulfonate (SDBS) aqueous solution into the polymer slurry medium and stirring evenly, then slowly pouring the negative electrode mixed powder into it, stirring at high speed to break it up, so as to prevent the negative electrode mixed powder from agglomerating after contacting the polymer slurry medium; then adding SBR emulsion and PTFE emulsion respectively, and finally adding zinc powder and carbon material to prepare the battery negative electrode slurry;
[0017] Step (4): Preparation of the negative electrode of the zinc-nickel battery: coating, drying, rolling, cutting, welding and extending the pole ear and coating the diaphragm to prepare the negative electrode of the zinc-nickel battery;
[0018] The polymer slurry medium is formed by mixing a polymer matrix and a base reinforcing agent; the polymer matrix is selected from one of a polyvinyl alcohol (PVA) aqueous solution, a polyethylene oxide (PEO) aqueous solution, and a polyethylene-vinyl acetate copolymer (EVA) aqueous solution; the base reinforcing agent is selected from a carboxymethyl cellulose (CMC) aqueous solution; the mass ratio of the polymer matrix to the base reinforcing agent solution is (20-25): (1-10);
[0019] The concentration of the polymer matrix is 2% to 5%, and the concentration of the substrate strengthening agent solution is 2% to 5%;
[0020] The SBR emulsion is an SBR aqueous solution with an SBR solid content of 50%;
[0021] The PTFE emulsion is a PTFE aqueous solution with a PTFE resin solid content of 60%;
[0022] The carbon material is one or more of colloidal graphite with a lamellar structure, graphene, conductive carbon black with a porous structure, and carbon nanotubes.
[0023] Preferably, the high-speed stirring speed in step (3) is 1500-2000 r / min.
[0024] Preferably, the step (4) specifically comprises the following steps: pre-pressing the punched tin-plated copper strip base to a thickness of 0.70-0.80 mm, then coating the slurry on the punched tin-plated copper strip and setting the scraper gap to 0.75 mm to scrape and integrate the material to obtain a punched tin-plated copper strip uniformly coated with the slurry; then drying the coated punched tin-plated copper strip at 60-80°C for 1-4 hours, and then rolling it twice on a roller press, and obtaining a negative electrode sheet after the two rollings are completed. Then, it is cut into a specific shape and size, and a nickel extension tab with tab glue is welded to the cut trapezoidal tab by a spot welder, and finally a layer of PP diaphragm is coated around the negative electrode sheet to fully cover the reaction surface area of the tab, and finally a negative electrode of a zinc-nickel battery is obtained.
[0025] Preferably, the solid negative electrode active material is zinc oxide;
[0026] The negative electrode additive is one or more of metal single substance Bi powder, Sn powder, bismuth oxide, indium hydroxide, calcium hydroxide, aluminum oxide or lead oxide metal compound.
[0027] Preferably, the negative electrode additive is a combination of metal single substance Bi powder or Sn powder and indium hydroxide, with a weight ratio of (1-4): (0.05-2).
[0028] A zinc-nickel battery negative electrode is prepared by using the above-mentioned method for preparing the zinc-nickel battery negative electrode.
[0029] As preferably, the following components by weight are included:
[0030] 50-70 parts of solid negative electrode active material
[0031] Zn powder 8-15 parts
[0032] Negative electrode additive 2-8 parts
[0033] 1-5 parts of carbon material
[0034] 0.3-0.7 parts of sodium dodecylbenzene sulfonate (SDBS) aqueous solution
[0035] 20-30 parts of polymer slurry medium
[0036] SBR emulsion 1-6 parts
[0037] PTFE emulsion 3-5 parts
[0038] A zinc-nickel battery is assembled from the above-mentioned zinc-nickel battery negative electrode and zinc-nickel battery positive electrode sheet.
[0039] The beneficial effects of the present invention are as follows:
[0040] (1) An ionically conductive polymer binder and an electronically conductive surfactant are added to the polymer slurry medium to form an organic polymer framework with ion and electronic conductivity. The viscoelasticity and conductivity of individual polymers work together to improve the capacity of the electrode and the stability under high discharge rates. Among them, the added polymer base reinforcement CMC solution has a better dispersion effect on the active substance and other powder materials than the PAAK solution, effectively avoiding the phenomenon that the powder is easy to agglomerate during the stirring process, resulting in uneven slurry and difficulty in slurrying. Figure 4 A schematic diagram of the slurry prepared by adding PAAK is shown, and the agglomeration phenomenon is quite obvious.
[0041] (2) The mixed negative electrode powder is added to the polymer slurry medium under high-speed stirring, so that the active material and the negative electrode additive are evenly dispersed and fully contacted, thereby improving their cycle performance. In addition, high-speed stirring is also more conducive to the uniform formation of the slurry.
[0042] (3) Compared with the traditional single binder, the use of composite binder can improve the adhesion between the active material of the electrode and the substrate, thereby effectively improving the phenomenon of powder shedding in the late stage of zinc-nickel battery cycle, which leads to a significant decrease in capacity.
[0043] (4) Introducing carbon materials into the organic framework of the electrode to build an efficient conductive network in the negative electrode, improving the ability of the electrode to conduct electrons, thereby reducing the polarization of the electrode. In addition, carbon materials with porous or layered structures can also effectively increase the contact area between the electrolyte and the electrode, allowing more active substances to participate in the reaction. The two work synergistically to improve the charging acceptance of the electrode, effectively improving the charging and discharging efficiency and capacity of the electrode.
[0044] (5) The intertwined long-chain polymers in the electrode network interact with the porous carbon material or layered carbon material to jointly construct a transmission channel for zincate ions, improve the deposition and stripping of zinc, inhibit dendrite formation and electrode passivation, and thus improve the cycle life.
[0045] (6) The use of a colloidal polymer slurry medium has the advantages of being easy to store, stable in alkaline solution, and having uniform dispersion of the components.
[0046] (7) A specific order of adding materials is adopted to add materials to the polymer slurry medium in batches, accompanied by high-speed stirring, to minimize agglomeration during slurry stirring, improve slurry dispersion, and improve electrode consistency. In addition, a detailed description of the process control points in subsequent slurry coating, drying, and rolling is provided, which has a good guiding significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0048] Figure 1 This is a schematic diagram of the slurry in Example 1 of the present application;
[0049] Figure 2 This is a schematic diagram of the negative electrode of this application;
[0050] Figure 3 This is a schematic diagram of the negative electrode sheet of Example 1 of the present application;
[0051] Figure 4 This is a schematic diagram of the slurry of Comparative Example 3 of the present application having obvious agglomeration phenomenon;
[0052] Figure 5 The voltage-current-time comparison diagram (Figure a) and the coulomb efficiency-cycle number comparison diagram (Figure b) of Example 1 of the present application and a commercially available electrode under full battery testing;
[0053] Figure 6 The voltage, current-time diagram (Figure a) and the coulombic efficiency-cycle number diagram (Figure b) of the full battery test of Example 5 of the present application are shown;
[0054] Figure 7 The voltage, current-time diagram (Figure a) and the coulombic efficiency-cycle number diagram (Figure b) of the full battery test of Example 6 of the present application are shown;
[0055] Figure 8 This is a schematic diagram of the slurry fineness measurement results of Example 1 of the present application; DETAILED DESCRIPTION
[0056] In order to enable those skilled in the art to better understand the technical solutions in the embodiments of the present invention and to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are further described below.
[0057] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0058] Embodiment 1:
[0059] A zinc-nickel battery negative electrode slurry comprises the following components in parts by weight: 51.12 parts of medical-grade zinc oxide as a solid negative electrode active material, 12.5 parts of Zn powder with a mesh size of 500 or more, 3.08 parts of a negative electrode additive, which is a metal single substance Bi and indium hydroxide in a weight ratio of 2:0.08 parts, 1 part of colloidal graphite as a carbon material, 0.5 parts of a sodium dodecylbenzene sulfonate (SDBS) aqueous solution with a 10% SDBS solid content as a surfactant, 1.8 parts of an SBR aqueous solution with a 50% SBR solid content, 4 parts by weight of a PTFE aqueous solution with a 60% PTFE resin solid content, and 27 parts of a polymer slurry medium, which comprises a 4% polyvinyl alcohol solution and a 3% sodium carboxymethyl cellulose aqueous solution in a ratio of 22:5, wherein the 4% polyvinyl alcohol solution is a solution obtained by dissolving 4 parts of polyvinyl alcohol in 96 parts of a deionized water solution, and the 3% sodium carboxymethyl cellulose aqueous solution is a solution obtained by dissolving 3 parts of sodium carboxymethyl cellulose in 97 parts of a deionized water solution.
[0060] A method for preparing a negative electrode of a zinc-nickel battery comprises the following steps:
[0061] Step (1): negative electrode powder mixing: the solid negative electrode active material and the negative electrode additive are fully stirred to obtain a negative electrode mixed powder, and then the required zinc powder and carbon material are also pre-mixed to obtain a negative electrode mixed powder;
[0062] Step (2): preparing a polymer slurry medium: preparing different solutions in the polymer slurry medium in advance, mixing and stirring the different solutions to obtain a polymer slurry medium:
[0063] Step (3): slurry preparation, adding a surfactant sodium dodecylbenzene sulfonate (SDBS) aqueous solution into the polymer slurry medium and stirring evenly, then slowly pouring the negative electrode mixed powder into it, stirring at a high speed of 1600r / min to disperse it, so as to prevent the negative electrode mixed powder from agglomerating after contacting the polymer slurry medium; then adding SBR emulsion and PTFE emulsion respectively and continuing to stir for 2 minutes, and finally adding zinc powder and carbon material mixed powder and stirring for 1 minute to obtain a battery negative electrode slurry; Figure 1 shown.
[0064] Step (4): Preparation of the negative electrode of zinc-nickel battery: The negative electrode of zinc-nickel battery is prepared by coating, drying, rolling, cutting, welding and extending the pole ear and coating the diaphragm; specifically, the prepared slurry is coated on the punched tin-plated copper strip substrate with a scraper, wherein the punched tin-plated copper strip substrate is pre-pressed to a thickness of 0.73 mm, and then the slurry is coated on the punched tin-plated copper strip and the scraper gap is set to 0.75 mm for scraping and integration to obtain a punched tin-plated copper strip uniformly coated with the slurry. Subsequently, the coated punched tin-plated copper strip is dried at 70° C. in a blast drying oven for 2 hours, and then rolled twice by a roller press, wherein the roller gap is set to 0.50 mm for the first rolling and 0.42 mm for the second rolling, and the negative electrode sheet is obtained after the two rollings are completed. Then cut it into a size of 9.4cm×7.7cm, cut out the shape of the pole ear, and weld the nickel extension pole ear with pole ear glue to the trapezoidal pole ear above the pole piece by a spot welding machine, such as Figure 2 The schematic diagram of the negative electrode of the zinc-nickel battery is shown in FIG. Finally, a layer of PP diaphragm is coated around the negative electrode plate to fully cover the reaction surface area of the plate. The prepared negative electrode of the zinc-nickel battery is as shown in FIG. Figure 3 As shown;
[0065] The prepared negative electrode sheet was assembled with a commercial positive electrode into a zinc-nickel battery, and the full battery was subjected to a full battery cycle test at a discharge rate of 8C and a DOD of 8%.
[0066] The subsequent embodiments and comparative examples are expressed in the same way.
[0067] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.10g / cm 3 , the fineness is 38μm, and the slurry is evenly dispersed, which is beneficial to improving the coating conditions and enhancing the stability of the electrode.
[0068] The prepared negative electrode loading is 110.5 mg / cm 2 The discharge capacity of the assembled full battery reached 425.8 mAh / g, and it cycled stably for more than 3500 times at a high discharge rate of 8C, showing excellent stability. In addition, we also compared the pole piece of the present invention with the pole piece on the market. Figure 5 It can be seen that the commercially available electrode can hardly support high-rate cycling, and the voltage of the first cycle is already very low. In addition, the coulomb efficiency of the commercially available electrode is unstable, and the fluctuation is very strong after 600 cycles, and the average coulomb efficiency is less than 80%. In comparison, the electrode of the present invention has better stability, and the coulomb efficiency exceeds 93%.
[0069] The discharge specific capacity is obtained from the test system in Table 3, specifically the discharge specific capacity measured in step 5.
[0070] The cycle test method is shown in Table 4: First, the first step is 13.82mA / cm2 Constant current charging to 1.9V is converted to constant voltage charging. The jump condition is time ≥ 5h or current ≤ 0.05A. The second step is to stand for 10s. The third step is 138.16mA / cm 2 Constant current discharge, the jump condition is time ≥ 36s or voltage ≤ 0.7V, the fourth step is to stand for 30s, the fifth step is 27.63mA / cm 2 After constant current charging to 1.9V, switch to constant voltage charging. The jump condition is time ≥ 5min or current ≤ 0.2A, and then cycle according to steps 2 to 5.
[0071] Embodiment 2:
[0072] Compared with Example 1, the difference of this example is that the polyvinyl alcohol solution is replaced by a polyethylene oxide (PEO) aqueous solution.
[0073] The viscosity of the prepared slurry is about 10000mpa·s and the density is 2.11g / cm 3 , the fineness is 39μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 109.8mg / cm 2 The assembled full-battery discharge capacity reached 405.2mAh / g, and it could be stably cycled for more than 2500 times at a high discharge rate of 8C.
[0074] Embodiment 3:
[0075] Compared with Example 1, the difference of this example is that the polyvinyl alcohol solution is replaced by a polyethylene-vinyl acetate copolymer (EVA) aqueous solution.
[0076] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.09g / cm 3 , the fineness is 38μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 109.6mg / cm 2 The assembled full-battery discharge capacity reached 406.9 mAh / g, and it could be stably cycled for more than 2400 times at a high discharge rate of 8C.
[0077] Embodiment 4:
[0078] Compared with Example 1, the difference of this example is that the 3% sodium carboxymethyl cellulose aqueous solution is replaced by a 2% sodium carboxymethyl cellulose aqueous solution.
[0079] The viscosity of the obtained slurry is about 9000mpa·s and the density is 2.02g / cm 3, the fineness is 36μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 102.9mg / cm 2 The assembled full-battery discharge capacity reached 410.6 mAh / g, and it could be stably cycled for more than 2800 times at a high discharge rate of 8C.
[0080] Embodiment 5:
[0081] Compared with Example 1, the difference of this example is that the 3% sodium carboxymethyl cellulose aqueous solution is replaced by a 5% sodium carboxymethyl cellulose aqueous solution.
[0082] The viscosity of the obtained slurry is about 11000mpa·s and the density is 2.23g / cm 3 , the fineness is 37μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 115.1mg / cm 2 The assembled full battery discharge capacity reaches 419.5 mAh / g. As shown in Figure 6, the voltage, current-time diagram and coulombic efficiency-cycle number diagram of this embodiment show that the stable cycle exceeds 3500 cycles at a high discharge rate of 8C, and its coulombic efficiency is higher than 92%, so this embodiment is one of the preferred examples.
[0083] Embodiment 6:
[0084] Compared with Example 1, the difference of this example is that the weight portion of colloidal graphite is 3 parts.
[0085] The viscosity of the obtained slurry is about 10500mpa·s and the density is 2.13g / cm 3 , the fineness is 38μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 112.3mg / cm 2 , the assembled full battery discharge capacity reaches 422.3mAh / g, and, as Figure 7 The voltage, current-time diagram and coulomb efficiency-cycle number diagram of this embodiment are shown. It can be seen that it can stably cycle more than 3500 times at a high discharge rate of 8C, and the coulomb efficiency is higher than 91%, so this embodiment is one of the preferred examples.
[0086] Embodiment 7:
[0087] Compared with Example 1, the difference of this example is that: 1 part of SBR aqueous solution with SBR solid content of 50% is used.
[0088] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.08g / cm 3, the fineness is 36μm, the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 108.1mg / cm 2 The assembled full-battery discharge capacity reached 415.6 mAh / g, and it could be stably cycled for more than 2800 times at a high discharge rate of 8C.
[0089] Embodiment 8:
[0090] Compared with Example 1, the difference of this example is that: 6 parts of SBR aqueous solution with SBR solid content of 50% are used.
[0091] The viscosity of the obtained slurry is about 11000mpa·s and the density is 2.14g / cm 3 , the fineness is 40μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 112.2mg / cm 2 The assembled full-battery discharge capacity reached 416.2 mAh / g, and it could be stably cycled for more than 2800 times at a high discharge rate of 8C.
[0092] Embodiment 9:
[0093] Compared with Example 1, the difference of this example is that the weight portion of the PTFE aqueous solution with a PTFE resin solid content of 60% is 3 parts.
[0094] The viscosity of the obtained slurry is about 10500mpa·s and the density is 2.10g / cm 3 , the fineness is 37μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 109.9mg / cm 2 The assembled full-battery discharge capacity reached 415.7 mAh / g, and it could be stably cycled for more than 2500 times at a high discharge rate of 8C.
[0095] Embodiment 10:
[0096] Compared with Example 1, the difference of this example is that the weight portion of the PTFE aqueous solution with a PTFE resin solid content of 60% is 5 parts.
[0097] The obtained slurry has a viscosity of about 9500 mpa·s and a density of 2.15 g / cm 3 , the fineness is 40μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 112.6mg / cm 2 The assembled full-battery discharge capacity reached 414.8 mAh / g, and it could be stably cycled for more than 2500 times at a high discharge rate of 8C.
[0098] Embodiment 11:
[0099] Compared with Example 1, the difference of this example is that the negative electrode additives are metal single substance Sn powder and indium hydroxide.
[0100] The obtained slurry has a viscosity of about 10000 mpa·s and a density of 2.09 g / cm 3 , the fineness is 38μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 110.2mg / cm 2 The assembled full-battery discharge capacity reached 418.4 mAh / g, and it could be stably cycled for more than 3000 times at a high discharge rate of 8C.
[0101] Embodiment 12:
[0102] Compared with Example 1, the difference of this example is that the negative electrode additives are bismuth oxide and indium hydroxide.
[0103] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.10g / cm 3 , the fineness is 37μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 110.7mg / cm 2 The assembled full-battery discharge capacity reached 413.8 mAh / g, and it could be stably cycled for more than 2800 times at a high discharge rate of 8C.
[0104] Embodiment 13:
[0105] Compared with Example 1, the difference of this embodiment is that: in step (3), the dispersion is accompanied by high-speed stirring at 2000 r / min.
[0106] The viscosity of the obtained slurry is about 10500mpa·s and the density is 2.09g / cm 3 , the fineness is 38μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 110.4mg / cm 2 The assembled full-battery discharge capacity reached 419.1 mAh / g, and it could be stably cycled for more than 3000 times at a high discharge rate of 8C.
[0107] Embodiment 14:
[0108] Compared with Example 1, the difference of this embodiment is that: in step (3), the dispersion is accompanied by high-speed stirring at 1500 r / min.
[0109] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.10g / cm3 , the fineness is 39μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 109.5mg / cm 2 The assembled full-battery discharge capacity reached 418.2 mAh / g, and it could be stably cycled for more than 3000 times at a high discharge rate of 8C.
[0110] Comparative Example 1:
[0111] Compared with Example 1, the difference of this comparative example is that the polymer slurry medium is entirely replaced by deionized water.
[0112] The viscosity of the obtained slurry is about 8500mpa·s and the density is 2.01g / cm 3 , the fineness is 34μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 100.2mg / cm 2 The assembled full-battery discharge capacity reached 403.6 mAh / g, and it could be stably cycled for more than 2000 times at a high discharge rate of 8C.
[0113] Comparative Example 2:
[0114] Compared with Example 1, the difference of this comparative example is that the 4% polyvinyl alcohol solution in the polymer slurry medium is replaced by deionized water.
[0115] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.06g / cm 3 , the fineness is 36μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 107.9mg / cm 2 The assembled full-battery discharge capacity reached 405.8 mAh / g, and it could be stably cycled for more than 2,300 times at a high discharge rate of 8C.
[0116] Comparative Example 3:
[0117] Compared with Example 1, the difference of this comparative example is that the sodium carboxymethyl cellulose aqueous solution in the polymer slurry medium is replaced by potassium polyacrylate (PAAK) solution.
[0118] The viscosity of the obtained slurry is about 11500mpa·s and the density is 2.15g / cm 3 , fineness is 42μm, slurry such as Figure 4 As shown in the figure, there is a more obvious agglomeration phenomenon, which will affect the coating conditions and the stability of the electrode. The prepared negative electrode loading is 116.9 mg / cm 2The assembled full-battery discharge capacity reached 413.7 mAh / g, and it could be stably cycled for more than 2000 times at a high discharge rate of 8C.
[0119] Comparative Example 4:
[0120] Compared with Example 1, the difference of this comparative example is that the weight portion of the negative electrode additive is 0 part.
[0121] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.10g / cm 3 , the fineness is 39μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 110.1mg / cm 2 The assembled full-battery discharge capacity reached 407.9 mAh / g, and it could be stably cycled for more than 1500 times at a high discharge rate of 8C.
[0122] Comparative Example 5:
[0123] Compared with Example 1, the difference of this comparative example is that the negative electrode additive is indium hydroxide, and the weight portion is 0.08 parts.
[0124] The obtained slurry has a viscosity of about 10000 mpa·s and a density of 2.09 g / cm 3 , the fineness is 37μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 111.4mg / cm 2 The assembled full-battery discharge capacity reached 409.4 mAh / g, and it could be stably cycled for more than 1,800 cycles at a high discharge rate of 8C.
[0125] Comparative Example 6:
[0126] Compared with Example 1, the difference of this comparative example is that the weight portion of the SBR aqueous solution with an SBR solid content of 50% is 0.
[0127] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.07g / cm 3 , the fineness is 36μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 107.3mg / cm 2 The assembled full-battery discharge capacity reached 406.2mAh / g, and it could be stably cycled for more than 2300 times at a high discharge rate of 8C.
[0128] Comparative Example 7:
[0129] Compared with Example 1, the difference of this comparative example is that the weight portion of the PTFE aqueous solution with a PTFE resin solid content of 60% is 0.
[0130] The viscosity of the obtained slurry is about 10500mpa·s and the density is 2.10g / cm 3 , the fineness is 36μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 106.8mg / cm 2 The assembled full-battery discharge capacity reached 405.2mAh / g, and it could be stably cycled for more than 2000 times at a high discharge rate of 8C.
[0131] Comparative Example 8:
[0132] Compared with Example 1, the difference of this comparative example is that the preparation method comprises the following steps:
[0133] Step (1): preparing a polymer slurry medium: preparing different solutions in the polymer slurry medium in advance, mixing and stirring the different solutions to obtain a polymer slurry medium:
[0134] Step (3): Slurry preparation: solid active material, negative electrode additive, SDBS, carbon material, and zinc powder are added to the slurry medium, and dispersed with high-speed stirring at 1500r / min, and then SBR emulsion and PTFE emulsion are added respectively and stirring is continued for 2 minutes to obtain battery negative electrode slurry.
[0135] The viscosity of the obtained slurry is about 10500mpa·s and the density is 2.11g / cm 3 , the fineness is 42μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 111.9mg / cm 2 The assembled full-battery discharge capacity reached 414.2 mAh / g, and it could be stably cycled for more than 2000 times at a high discharge rate of 8C.
[0136] Comparative Example 9:
[0137] Compared with Example 1, the difference of this comparative example is that in step (3), the stirring and breaking up is accompanied with a stirring speed of 1000 r / min.
[0138] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.08g / cm 3 , the fineness is 43μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 111.3mg / cm 2 The assembled full-battery discharge capacity reached 412.2 mAh / g, and it could be stably cycled for more than 2000 times at a high discharge rate of 8C.
[0139] Comparative Example 10:
[0140] Compared with Example 1, the difference of this comparative example is that: in step (3), the mixture is dispersed with high-speed stirring at 2500 r / min.
[0141] The viscosity of the obtained slurry is about 10000mpa·s and the density is 2.12g / cm 3 , the fineness is 38μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 109.4mg / cm 2 The assembled full-battery discharge capacity reached 413.2 mAh / g, and it could be stably cycled for more than 2500 times at a high discharge rate of 8C.
[0142] Comparative Example 11:
[0143] Compared with Example 1, the difference of this comparative example is that the weight portion of colloidal graphite is 0 part.
[0144] The viscosity of the prepared slurry is about 10000mpa·s and the density is 2.11g / cm 3 , the fineness is 38μm, and the slurry is evenly dispersed, which is conducive to improving the coating conditions and improving the stability of the electrode. The prepared negative electrode loading is 110.6mg / cm 2 The assembled full-battery discharge capacity reached 410.8 mAh / g, and it could be stably cycled for more than 2000 times at a high discharge rate of 8C.
[0145] The slurry parameter table of the embodiments of the present application and the comparative examples is shown in Table 1 below, the electrode parameters and the full battery performance are shown in Table 2, the discharge specific capacity test system is shown in Table 3 below, and the cycle test system is shown in Table 4 below.
[0146] Table 1. Slurry parameters of the examples and comparative examples of the present application
[0147]
[0148] The viscosity test uses a rotational viscometer. First, ensure that the sample temperature is maintained at 23±0.5℃, then start the viscometer rotor, and read the value after the viscometer reading stabilizes. Take two samples for testing until the difference between the values of the two samples tested continuously is less than 3%. The average value of the two is taken, referring to the single-cylinder rotation method in "GB / T 2794-2022 Determination of viscosity of adhesives";
[0149] The fineness test uses a QXC single-slot scraper fineness meter with a range of 150μm for measurement, and is tested in accordance with the national standard "GB / T 6753.1-2007 Determination of grinding fineness of paints, varnishes and printing inks". Figure 8 This is a schematic diagram of the slurry fineness test of Example 1;
[0150] Table 2. Table of pole piece parameters and full battery performance of the embodiments of the present application and the comparative examples
[0151]
[0152]
[0153] Table 3. Full battery capacity test system
[0154]
[0155] Table 4 Full battery cycle test system
[0156]
[0157] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations made to these embodiments without departing from the principles and spirit of the present invention still fall within the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode of a zinc-nickel battery, characterized in that: The steps include: Step (1): negative electrode powder mixing: the solid negative electrode active material and the negative electrode additive are fully stirred to obtain a negative electrode mixed powder; then the required zinc powder and carbon material are also pre-mixed to obtain a negative electrode mixed powder; Step (2): preparing a polymer slurry medium: preparing different solutions in the polymer slurry medium in advance, mixing and stirring the different solutions to obtain a polymer slurry medium: Step (3): slurry preparation, adding a surfactant sodium dodecylbenzene sulfonate (SDBS) aqueous solution into the polymer slurry medium and stirring evenly, then slowly pouring the negative electrode mixed powder into it, stirring at high speed to break it up, so as to prevent the negative electrode mixed powder from agglomerating after contacting the polymer slurry medium; then adding SBR emulsion and PTFE emulsion respectively, and finally adding zinc powder and carbon material to prepare the battery negative electrode slurry; Step (4): negative electrode preparation: preparing a negative electrode for a zinc-nickel battery by coating, drying, rolling, cutting, welding and extending the tabs and coating the separator; The polymer slurry medium is formed by mixing a polymer matrix and a base reinforcing agent; the polymer matrix is selected from one of a polyvinyl alcohol (PVA) aqueous solution, a polyethylene oxide (PEO) aqueous solution, and a polyethylene-vinyl acetate copolymer (EVA) aqueous solution; the base reinforcing agent is a carboxymethyl cellulose (CMC) aqueous solution; the mass ratio of the polymer matrix to the base reinforcing agent solution is (20-25): (1-10); The concentration of the polymer matrix is 2% to 5%, and the concentration of the base reinforcing agent is 2% to 5%; The SBR emulsion is an SBR aqueous solution with an SBR solid content of 50%; The PTFE emulsion is a PTFE aqueous solution with a PTFE resin solid content of 60%; The carbon material is one or more of colloidal graphite with a lamellar structure, graphene, conductive carbon black with a porous structure, and carbon nanotubes.
2. A method for preparing a negative electrode for a zinc-nickel battery as claimed in claim 1, characterized in that: The high-speed stirring speed in step (3) is 1500-2000 r / min.
3. A method for preparing a negative electrode for a zinc-nickel battery as claimed in claim 1, characterized in that: The step (4) specifically comprises the following steps: coating the prepared slurry onto a punched tin-plated copper strip substrate, specifically pre-pressing the punched tin-plated copper strip substrate to a thickness of 0.70-0.80 mm, then coating the slurry onto the punched tin-plated copper strip and setting the scraper gap to 0.75 mm to perform scraping and integration to obtain a punched tin-plated copper strip uniformly coated with the slurry; then drying the coated punched tin-plated copper strip at 60-80° C. for 1-4 h, then rolling it twice on a roller press, and obtaining a negative electrode sheet after the two rolling steps; then cutting it into a specific shape and size, and welding a nickel extended electrode ear with an electrode ear glue to the cut trapezoidal electrode ear by a spot welding machine, and finally coating a layer of PP diaphragm around the negative electrode sheet to fully cover the reaction surface area of the negative electrode sheet, thereby finally obtaining a negative electrode for a zinc-nickel battery.
4. A method for preparing a negative electrode for a zinc-nickel battery as claimed in claim 1, characterized in that: The solid negative electrode active material is zinc oxide; The negative electrode additive is one or more of metal single substance Bi powder, Sn powder, bismuth oxide, indium hydroxide, calcium hydroxide, aluminum oxide or lead oxide metal compound.
5. A method for preparing a negative electrode for a zinc-nickel battery as claimed in claim 1, characterized in that: The negative electrode additive is a combination of metal single substance Bi powder or Sn powder and indium hydroxide, and the weight ratio is (1-4): (0.05-2).
6. A negative electrode for a zinc-nickel battery, characterized in that: The negative electrode of the zinc-nickel battery is prepared by the method for preparing the negative electrode of the zinc-nickel battery according to any one of claims 1 to 5.
7. A negative electrode for a zinc-nickel battery as claimed in claim 6, characterized in that: It includes the following components by weight: 50-70 parts of solid negative electrode active material Zn powder 8-15 parts Negative electrode additive 2-8 parts 1-5 parts of carbon material 0.3-0.7 parts of sodium dodecylbenzene sulfonate (SDBS) aqueous solution 20-30 parts of polymer slurry medium SBR emulsion 1-6 parts 3-5 parts of PTFE emulsion.
8. A zinc-nickel battery, characterized in that: The nickel-zinc battery is assembled from the negative electrode of the nickel-zinc battery as claimed in claim 6 or 7 and the positive electrode of the nickel-zinc battery.
Citation Information
Patent Citations
Zinc-nickel battery negative electrode active substance, zinc-nickel battery negative electrode plate and zinc-nickel battery
CN105161702A
A paste for the negative electrode of a zinc-nickel battery and its preparation method
CN110289395B
Nickel-zinc battery positive electrode and preparation method and application thereof
CN119050286A
High-performance long-life zinc-nickel battery negative electrode slurry
CN111193009A
Method for preparing power type columnar sealed zinc-nickel alkaline accumulator zinc negative pole
CN1828983A